Respiratory Therapy in Patients with Acute Lung Injury and Concomitant Pneumothorax - Yu. V. Marchenkov; O. A. Morozova; D. A. Ostapchenko (Общая реаниматология)
Objective. To comparatively study the efficiency of respiratory support using biphasic positive airway pressure (BIPAP), spontaneous intermittent mandatory ventilation (SIMV), and intermittent positive pressure ventilation (IPPV) in patients with acute lung injury (ALI) and concomitant pneumothorax. Subjects and materials. Sixty-eight patients were examined. The severity of disease was 18 to 24 APACHE II scores. After elimination of pneumothorax, lung opening maneuver was made by the routine procedure 1—2 times daily on different types of respiratory support. Results. The study has indicated that in patients with ALI and concomitant pneumothorax, BIPAP reduces the time of pleural cavity drainage, which allows the lung opening maneuver to be earlier used. Conclusion. BIPAP leads to a better adaptation of a patient to respiratory support, to the limited use of sedatives, and to better gas exchange in the lung and accelerates transfer from total respiratory support to spontaneous breathing. Key words: acute lung injury, pneumothorax, BIPAP, lung opening maneuver.